2011 IEEE International Conference on Dielectric Liquids 2011
DOI: 10.1109/icdl.2011.6015432
|View full text |Cite
|
Sign up to set email alerts
|

Accumulative effect on streamer propagation of lightning impulses on oil/pressboard interface

Abstract: This paper reports the accumulative effect of multiple negative lightning impulse shots on streamer propagation along liquid/pressboard surface. Pressboards impregnated with the insulating liquids including a mineral oil, a natural ester and a synthetic ester were tested under a pointplane divergent field. Streamer propagation was recorded by a high speed intensified CCD camera. In addition, current and light signals were monitored by non-inductive current shunt and photo multiplier tube (PMT) respectively. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…In 2011, the development processes of streamers at the interface between oil and OIP were observed [124, 125]. The authors of the cited studies found that, under the application of repetitive lightning impulses, the length of the streamer grows with an increasing number of impulse applications.…”
Section: Accumulative Failure Of Oil–paper Insulationmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2011, the development processes of streamers at the interface between oil and OIP were observed [124, 125]. The authors of the cited studies found that, under the application of repetitive lightning impulses, the length of the streamer grows with an increasing number of impulse applications.…”
Section: Accumulative Failure Of Oil–paper Insulationmentioning
confidence: 99%
“…However, this phenomenon was not detected when the OIP was removed. This indicates that the accumulative effect appears not only during dielectric breakdown but also on flashover at the oil–paper interface [124, 125].…”
Section: Accumulative Failure Of Oil–paper Insulationmentioning
confidence: 99%
“…A wide characterization of the inception and propagation of 2nd mode positive streamers have been performed by several authors along liquid/solid interfaces [11][12][13][14][15]. Different studies report the influence of the thickness and permittivity of the solid on the current, charge and shape of the streamer filaments [11,[15][16][17][18][19][20][21], the existence of a potential gradient across the streamer [8,13,14], the accumulative effect of multiple streamers initiated at a liquid/solid interface and the influence of the chemical composition of the oil [15,21,22], etc. All these studies highlight the importance of the bulk properties of the solid material (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…This type of discharges (creeping discharges) has been the subject of numerous studies [1][2][3][4][5][6][7][8][9][10][11][12][13]. It appears from the different results reported in the literature that the morphology of these discharges and the associated characteristics depend among others things on the thickness of solid insulator and the dielectric constant of both constituents (insulator and oil).…”
Section: Introductionmentioning
confidence: 99%